3-Dimensional printing and bioprinting in neurological sciences: applications in surgery, imaging, tissue engineering, and pharmacology and therapeutics - Sreejita Dhar; Faraz Ahmad; Aditi Deshpande; Sandeep Singh Rana; Toufeeq Ahmed A; Swagatika Priyadarsini (Journal of Materials Science: Materials in Medicine)
Abstract The rapid evolution of three-dimensional printing (3DP) has significantly impacted the medical field. In neurology for instance, 3DP has been pivotal in personalized surgical planning and education. Additionally, it has facilitated the creation of implants, microfluidic devices, and optogenetic probes, offering substantial implications for medical and research applications. Additionally, 3D printed nasal casts are showing great promise for targeted brain drug delivery. 3DP has also aided in creating 3D “phantoms” aligning with advancements in neuroimaging, and in the design of intricate objects for investigating the neurobiology of sensory perception. Furthermore, the emergence of 3D bioprinting (3DBP), a fusion of 3D printing and cell biology, has created new avenues in neural tissue engineering. Effective and ethical creation of tissue-like biomimetic constructs has enabled mechanistic, regenerative, and therapeutic evaluations. While individual reviews have explored the applications of 3DP or 3DBP, a comprehensive review encompassing the success stories across multiple facets of both technologies in neurosurgery, neuroimaging, and neuro-regeneration has been lacking. This review aims to consolidate recent achievements of both 3DP and 3DBP across various neurological science domains to encourage interdisciplinary research among neurologists, neurobiologists, and engineers, in order to promote further exploration of 3DP and 3DBP methodologies to novel areas of neurological science research and practice. Graphical abstract